Improved 30 day heart failure rehospitalization prediction through the addition of device‐measured parameters. (13th September 2020) - Brown, Jason R.; Alonso, Alvaro; Mazimba, Sula; Warman, Eduardo N.; Bilchick, Kenneth C.
Abstract: Aims: This study aimed to improve in‐person clinical evaluation on the day of heart failure (HF) hospitalization discharge by adding device‐measured parameters to predict 30 day HF rehospitalization risk in cardiac resynchronization therapy‐defibrillator (CRT‐D) patients. Methods and results: In a cohort of Medicare patients with CRT‐Ds, the independent prognostic value of four device‐measured parameters was assessed relative to typical clinical parameters associated with rehospitalization risk. Medicare registry, claims, and Medtronic CareLink® Network data for these patients were analysed using logistic regression modelling and net reclassification methods. Among 1563 CRT‐D patients, 411 patients had 607 HF hospitalization events during a median 6.3 years of follow‐up. Compared with clinical variables alone, impedance measurements resulted in a 28% improvement between the predicted probabilities of having vs. not having a 30 day HF rehospitalization (relative integrated discrimination improvement = 0.28) and a net 42% improvement in the classification of 30 day HF rehospitalization events and non‐events after an index HF hospitalization (net reclassification index = 0.42; 95% CI: 0.10, 0.74). Conclusions: In CRT patients, intrathoracic impedance measurements improve prediction of 30 day HF rehospitalization over clinical characteristics alone. The present study provides supportive data for the routine evaluation of intrathoracic impedance prior to discharge in patient with CRT devices. Furthermore, the models developed in this study could be used to design interventions to improve compliance with Medicare reimbursement guidelines regarding 30 day HF rehospitalization.